Non-Exposed Endoscopic Wall-Inversion Surgery for Gastrointestinal Stromal Tumor of the Stomach: First Case Report in Korea - Da Won Kim; Joon Sung Kim; Byung-Wook Kim; Ji Yun Jung; Gi Jun Kim; Jin-Jo Kim (Korean Society of Gastrointestinal Endoscopy, 2016)
Laparoscopic wedge resection of the stomach is a widely accepted treatment for primary resectable gastrointestinal stromal tumors (GISTs). However, it is difficult to determine the appropriate incision line from outside of the stomach, and many attempts have been made to avoid unnecessary resection of unaffected gastric tissues. Recently a technique called non-exposed endoscopic wall-inversion surgery (NEWS) was introduced to avoid exposure of GIST to the peritoneum. Here, we describe the first published case of NEWS for GIST of the stomach practiced in Korea.